PENGARUH PESAN KAMPANYE 'DIET KANTONG PLASTIK' TERHADAP SIKAP MENGURANGI PENGGUNAAN KANTONG PLASTIK : Survei pada Followers Akun Instagram @Iddkp - Dhea Salsabila, (2020)
This research observes a campaign by Gerakan Indonesia Diet Kantong Plastik (GIDKP) titled 'Plastic Bag Diet' ('Diet Kantong Plastik'). The aim of this research is to know the impact of Plastic Bag Diet campaign towards Attitude reduces the Use of Plastic-Bags. The theory used to examine this research is Ostergaard's campaign model. The research method is quantitative. Data-gathering was done by spreading questionnaire among respondents. The population of this research is the followers of Instagram account @iddkp, sampled by the Yamane formula across 99 respondents. This research uses non-probability sampling technique with purposive sampling in order to generate answers from the samples. The findings show that the correlation between X variable ('Plastic Bag Diet' campaign message) and Y variable (Attitude reduces the Use of Plastic-Bags) is 0,745. Based on the determinant coefficient, it was found that there is 55,5% effect from X variable to Y variable. The t-test shows t-value > t-table with a result of 10,998 t-value > t-table 1,660 - which conclude rejected H0 and accepted Ha. This study concludes that there is strong effects from the 'Plastic Bag Diet' campaign towards Attitude reduces the Use of Plastic-Bags. This research advises Gerakan Indonesia Diet Kantong Plastik to continue its positive advocacy towards the environment and community as a whole, be it from its campaign or many other activities.